Business Ethics and the Management of Non-Profit Institutions - Bouckaert, Luk (Journal of business ethics, 1998)
The core of business ethics literature is based upon the stakeholder theory of the firm. The normative function of this theory is to internalise the concept of social responsibility into the definition of the firm (the firm as a social contract) and into the managerial practice (participative management, social and ethical audit). But why should we introduce this business ethics approach into the field of the non-profit sector, which by its origin and mission has already a strong social dimension? Is there a genuine dilemma of social responsibility in non-profjt institutions? The first part of the paper will give a more theoretical answer to this question. The second part will illustrate the relevance of the business ethics approach by presenting an empirical application of the stakeholer theory in the Belgian-Flemish non-profit sector.